Prenatal Sonographic Head Circumference and Cerebral Ventricle Width Measurements Before and After Open Fetal Myelomeningocele Repair – Prediction of Shunting During the First Year of Life - Vonzun, Ladina; Winder, Franziska Maria; Meuli, Martin; Moerlen, Ueli; Mazzone, Luca; Kraehenmann, Franziska; Huesler, Margareth; Zimmermann, Roland; Ochsenbein, Nicole (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose The aim of this study was to describe the sonographic evolution of fetal head circumference (HC) and width of the posterior horn of the lateral ventricle (Vp) after open fetal myelomeningocele (fMMC) repair and to assess whether pre- or postoperative measurements are helpful to predict the need for shunting during the first year of life.Patients & Methods All 30 children older than one year by January 2017 who previously had fMMC repair at the Zurich Center for Fetal Diagnosis and Therapy were included. Sonographic evolution of fetal HC and Vp before and after fMMC repair was assessed and compared between the non-shunted (N = 16) and the shunted group (N = 14). ROC curves were generated for the fetal HC Z-score and Vp in order to show their predictive accuracy for the need for shunting until 1 year of age.Results HC was not an independent factor for predicting shunting. However, the need for shunting was directly dependent on the preoperative Vp as well as the Vp before delivery. A Vp > 10 mm at evaluation for fMMC repair or > 15 mm before delivery identifies 100 % of the infants needing shunt placement at a false-positive rate of 44 % and 25 %, respectively. All fetuses with a Vp > 15 mm at first evaluation received a shunt.Conclusion Fetuses demonstrating a Vp of > 15 mm before in utero MMC repair are extremely likely to develop hydrocephalus requiring a shunt during the first year of life. This compelling piece of evidence must be appropriately integrated into prenatal counseling.
Keywords: fetal myelomeningocele repair; spina bifida; ventriculoperitoneal shunting; fetal head circumference; ventriculomegaly